2013
DOI: 10.1055/s-0033-1343069
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in MRI of Focal and Diffuse Malignancy of Bone Marrow

Abstract: Bone marrow is a ubiquitous component of musculoskeletal imaging studies. The ability to identify and characterize pathology accurately in the bone marrow can be challenging given the broad spectrum of imaging features of normal bone marrow. Knowledge regarding the ability to differentiate normal from abnormal marrow has been enhanced with MR imaging with numerous techniques available to aid in distinguishing benign from malignant lesions in the bone marrow. T1-weighted fast spin echo (FSE) and fluid-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Nonetheless, the marrow compartment remains an important reservoir for disease relapse since marrow MRD early after consolidation with immunotherapy was the strongest predictor of PFS and OS. 89 …”
Section: Lessons Learned From Clinical Trials Of Anti-gd2 Antibodiesmentioning
confidence: 99%
“…Nonetheless, the marrow compartment remains an important reservoir for disease relapse since marrow MRD early after consolidation with immunotherapy was the strongest predictor of PFS and OS. 89 …”
Section: Lessons Learned From Clinical Trials Of Anti-gd2 Antibodiesmentioning
confidence: 99%
“…High 18 F-FDG uptake of the brain and limited spatial resolution of PET images taken together create artifacts that hamper the inclusion of skull in IBI calculation, and focal lesions in this area must be analyzed independently. Although skull involvement is relatively common in MM, the bone sites most frequently and extensively affected by the disease are the spine, pelvis, sternum and proximal metaphyses of long bones, because adult bone marrow is predominantly confined in these sites 39,40 . In our sample of 59 patients, only three (5%) had cranial involvement, demonstrated by 18 F-FDG-PET/CT, all with relatively small lesions compared to those of the spine and pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…So, many authors concluded that T1WI of MRI is unbiased at determining intraosseous tumor compared to STIR sequences or T2WI with fat suppression. 3 , 10 But the transition zone including the microinfiltration of tumor may be easily overlooked on T1WI, causing the underestimation of the tumor range. As shown in the present study, the tumor size measured on T1WI was 4.82 ± 0.87 cm, that was smaller than that measured on specimen under microscope (5.20 ± 0.89 cm, P < .05).…”
Section: Discussionmentioning
confidence: 99%